Skrining Fitokimia dan Potensi Antilitiasis dari Ekstrak Etanol Daun Nusa Indah Putih (Mussaenda pubescens) - Emma Julin Pongoh; Rymond Jusuf Rumampuk; Dian Howan; Veyta Tamunu (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
The phytochemical screening and antilitiasis assay have been done on the ethanolic extract of nusa indah putih leaf (Mussaenda pubescens). The screening phyticemical results showed that the leaves of nusa indah putih (M. pubescens) positively contain alkaloids and flavonoids. Antilitiasis assay results showed effectiveness in improving urolithiasis rats at doses of 300 mg / kg BW better in improving kidney compared to dose 150 mg / kg BW with a concentration of 1.8 ml / rat.